2023
DOI: 10.1039/d3nj04704k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-infective potency study of a Ru-based complex bearing benzonitrile against Staphylococcus aureus

Ziying Huang,
Guijuan Jiang,
Yun Song
et al.

Abstract: Multi drug-resistant Gram-positive pathogens has became one of the most serious problems facing mankind today. To address this challenge, it is urgently needed to develop new antimicrobial agents which are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…As previously reported, complexes containing methyl or tert -butyl groups may exhibit enhanced antimicrobial activity against S. aureus . 39–46 Surprisingly, the MIC values under dark and light conditions did not show substantial variation, and it is speculated that the low dose of ruthenium complexes may not be sufficient to entirely inhibit the growth of bacteria and the inherent dark toxicity of this series of complexes against S. aureus . It can be observed that the MBC values of Ru1–Ru8 show significant changes before and after optical exposure, indicating that ruthenium complexes have photo-inactivation effects on S. aureus under blue light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, complexes containing methyl or tert -butyl groups may exhibit enhanced antimicrobial activity against S. aureus . 39–46 Surprisingly, the MIC values under dark and light conditions did not show substantial variation, and it is speculated that the low dose of ruthenium complexes may not be sufficient to entirely inhibit the growth of bacteria and the inherent dark toxicity of this series of complexes against S. aureus . It can be observed that the MBC values of Ru1–Ru8 show significant changes before and after optical exposure, indicating that ruthenium complexes have photo-inactivation effects on S. aureus under blue light irradiation.…”
Section: Resultsmentioning
confidence: 99%